The Impact of Digital Multimodal Composition on Writing Ability of Iranian EFL Learners with Respect to Their Self-Efficacy - Najmeh Maghsoudi; Mohammad Golshan; Amin Naeimi (Journal of Modern Research in English Language Studies)
Despite the increasing attention of researchers to digital multimodal composition in recent years and the importance of self-efficacy beliefs in the development of writing ability, the instruction of writing skill has still remained traditional in Iran. The present mixed-methods study was conducted to examine the joint effect of digital multimodal composition and self-efficacy on the writing ability of Iranian EFL learners. In so doing, two intact groups including 59 sophomore students at a university in southeastern Iran participated in the study. The participants were assigned into two comparison groups of multimodal (n = 30) and monomodal (n = 29) compositions. The multimodal group composed five digital essays while the monomodal group produced five paper-based essays during the semester. Moreover, both groups’ self-efficacy beliefs were assessed through Second Language Writer Self-Efficacy Scale after they finished composing their essays. At the final stage of the research, semi-structured interviews were run to elicit the participants’ perception about digital multimodal composition. The result of two-way MANOVA revealed that the multimodal group outperformed the monomodal group in terms of content, communicative achievement, and organization, but not in language component. Additionally, self-efficacy had a significant impact on the writing ability of both multimodal and monomodal groups regardless of the type of writing they produced. Besides, the thematic analysis of the interviews revealed that highly-efficacious learners had positive perception about multimodal composition. The study concludes with the necessity of reshaping educational practices for English writing instruction in Iran and fostering the learners’ self-efficacy in the composition processes.